29th Annual meeting of the Society for Immunotherapy of Cancer (SITC). Issue 1 (19th May 2015) - Hurwitz, Arthur A; Lee, Sylvia; Knox, Susan; Kohrt, Holbrook; Verdeil, Gregory; Romano, Emanuela; Margolin, Kim; Urba, Walter J; Speiser, Daniel E
Abstract : The 29 th annual meeting of the Society for Immunotherapy of Cancer (SITC) was held November 7-9, 2014 in National Harbor, MD and was organized by Dr. Arthur A. Hurwitz (National Cancer Institute), Dr. Kim A. Margolin (Stanford University), Dr. Daniel E. Speiser (Ludwig Center for Cancer Research, University of Lausanne) and Dr. Walter J. Urba (Earle A. Chiles Research Institute, Providence Cancer Center). This meeting included over 1, 600 registered participants from 28 separate countries, making it the largest SITC meeting held to date. It highlighted significant worldwide progress in the development and application of cancer immunology to the practice of clinical oncology, including advances in diagnosis, prognosis and therapy, utilizing several immunological pathways and mechanisms for a variety of oncologic conditions. Presentations and posters demonstrated that many concepts that had been pursued preclinically in the past are now being translated into clinical practice, with clear benefits for patients.